2022
DOI: 10.3390/cancers14010227
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Ceramide Kinase/C1P in Cancer Development and Progression

Abstract: Cancer cells rewire their metabolic programs to favor biological processes that promote cell survival, proliferation, and dissemination. Among this relevant reprogramming, sphingolipid metabolism provides metabolites that can favor or oppose these hallmarks of cancer. The sphingolipid ceramide 1-phosphate (C1P) and the enzyme responsible for its biosynthesis, ceramide kinase (CERK), are well established regulators of cell growth and survival in normal, as well as malignant cells through stress-regulated signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…Sphingomyelin is produced by ceramide and phosphatidylcholine, and the reaction is catalyzed by sphingomyelin synthase ( Morigny et al, 2020 ). Stress response, differentiation, proliferation, apoptosis and migration of tumor cells are all regulated by sphingolipids receptor, especially Cer, sphingosine-1-phosphate (S1P) and ceramide-1-phosphate (C1P) ( Pchejetski et al, 2008 ; Guillermet-Guibert et al, 2009 ; Huang et al, 2013 ; Gomez-Larrauri et al, 2020 ; Presa et al, 2020 ; Camacho et al, 2022 ). What’s more, sphingolipids are the most important elements of the lipid raft.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomyelin is produced by ceramide and phosphatidylcholine, and the reaction is catalyzed by sphingomyelin synthase ( Morigny et al, 2020 ). Stress response, differentiation, proliferation, apoptosis and migration of tumor cells are all regulated by sphingolipids receptor, especially Cer, sphingosine-1-phosphate (S1P) and ceramide-1-phosphate (C1P) ( Pchejetski et al, 2008 ; Guillermet-Guibert et al, 2009 ; Huang et al, 2013 ; Gomez-Larrauri et al, 2020 ; Presa et al, 2020 ; Camacho et al, 2022 ). What’s more, sphingolipids are the most important elements of the lipid raft.…”
Section: Discussionmentioning
confidence: 99%
“…1b). As CerK level is closely associated with ceramide and C1P [9], we assessed ceramide level using LC-MS and C1P level using ELISA approaches in both tissue types. Compared to normal ovarian cells, we found that ceramide and C1P levels were decreased by ∼30% and ∼60% in ovarian cancer, respectively (Fig.…”
Section: Expression Analysis Of Cerk Ceramide and C1p In Ovarian Cancermentioning
confidence: 99%
“…Ceramides are the hub of sphingolipid metabolism, are key lipids in energetic-metabolic pathways and signaling cascades, and have been linked to promotion of apoptosis and drug sensitivity [7,8]. In contrast, ceramide 1-phosphate (C1P) is a pleiotropic bioactive sphingolipid that facilitates growth, survival, senescence, and metastasis in cancer progression [9,10]. Ceramide kinase (CerK) is an enzyme that is responsible for C1P biosynthesis through phosphorylating ceramide [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CerK is a calcium ion-dependent enzyme that catalyzes the production of C1P in cells. Intracellular C1P can perform a variety of biological functions, including the stimulation of tumor cell growth, the stimulation of VEGF release, the inhibition of tumor cell apoptosis, the promotion of tumor inflammation, the regulation of angiogenesis, and the stimulation of tumor cell migration ( 83 85 ). C1P regulates the invasion and migration of different types of cancer cells, including breast, lung, prostate, pancreas or leukemia cells ( 83 ).…”
Section: The Value Of Sphingolipid Metabolism In Cancermentioning
confidence: 99%